Myocardial revascularization in the elderly patient: with or without cardiopulmonary bypass? - Iglézias,José Carlos Rossini (2003)
OBJECTIVE: To verify if there is advantage in myocardial revascularization the elderly without cardiopulmonary bypass (CPB) in relation to the use of the same, being considered the viability of complete myocardial revascularization (MR) and the hospital morbidity and mortality. METHOD: We prospectively studied a hundred consecutive, no randomized patients, with age > or = 70 years, submitted to the primary and isolated myocardial revascularization between January and December of 2000. The patients were divided in two groups, G1 - 50 patients operated with CPB and G2 - 50 patients operated without CPB. Univariate testing of variables was performed with chi-squared analysis in the SPSS 10.0 Program and a p value less than 0.005 was considered significant. RESULTS: There was no renal failure or myocardial infarction (MI) in both groups; the incidence of respiratory failure was identical in the two groups (4%); two patient of G1 they had Strokes, and 12 presented low output syndrome, occurrences not registered in G2. The need of ventilatory support > 24 hs was not significant between groups. Medium time of hospital stay was 21.8 and 11.7 days respectively (NS) and the survival after 30 days were similar in the two groups. The patients' of G1 eighty percent had more than two approached arteries, against only 48% of G2 (p < 0.0001). CONCLUSION: Because the largest number of grafts in the patients of G1, we can affirm that the use of CPB can provide a larger probability of complete RM.